2015
DOI: 10.15517/rbt.v63i1.14580
|View full text |Cite
|
Sign up to set email alerts
|

Leaf and fruit essential oil compositions of Pimenta guatemalensis (Myrtaceae) from Costa Rica

Abstract: Pimenta is a genus of flowering plants in the Myrtaceae family, which has about 15 species, mostly found in the Caribbean region of the Americas. Commonly used for culinary and medicinal purposes, the best known commercial species are allspice, P. dioica (P. officinalis) and bay rum, P. racemosa, but there is little information concerning P. guatemalensis. The aim of the present study was to identify the chemical composition of the leaf and fruit essential oils of P. guatemalensis. The extraction of essential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…N.E.Br. (Apocynaceae) flowers (Formisano et al, 2009), Camellia sinensis (L.) Kuntze (Theaceae) (Han, Zhou, Cui, & Fu, 2006) and essential oil of Pimenta guatemalensis (Lundell) Lundell (Chaverri & Cicció, 2015). Jabalpurwala, Smoot and Rouseff (2009), studying volatile compounds in flowers of different species of Citrus, also observed high levels of n-hexanol in Citrus grandis (L.) Osbeck (Rutaceae), and correlated the levels with the pollination by bees, which is crucial for reproduction due to self-incompatibility.…”
Section: Discussionmentioning
confidence: 99%
“…N.E.Br. (Apocynaceae) flowers (Formisano et al, 2009), Camellia sinensis (L.) Kuntze (Theaceae) (Han, Zhou, Cui, & Fu, 2006) and essential oil of Pimenta guatemalensis (Lundell) Lundell (Chaverri & Cicció, 2015). Jabalpurwala, Smoot and Rouseff (2009), studying volatile compounds in flowers of different species of Citrus, also observed high levels of n-hexanol in Citrus grandis (L.) Osbeck (Rutaceae), and correlated the levels with the pollination by bees, which is crucial for reproduction due to self-incompatibility.…”
Section: Discussionmentioning
confidence: 99%
“…Pimenta genus is an important myrtaceous taxa that encompasses 15 species, mostly found in the Americas Caribbean area, and commonly used for several medicinal purposes [ 9 , 10 ]. Pimenta dioica and Pimenta racemosa are the most recognized in that genus to exhibit potential pharmacological effects owing to its rich essential oil composition [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Myrtaceae family comprises of approximately 140 genera 4 . This family has significant economic value as species from various genera are cultivated worldwide for edible fruits ( Psidium guajava ), spices and essential oil ( P dioica), and for timber ( Eucalyptus globulus ) 5 . Essential oils are volatile liquids that give plants their unique aroma and are composed of numerous compounds.…”
Section: Introductionmentioning
confidence: 99%
“…The Pimenta genus has approximately 15 species which are mostly located in the Caribbean and Central America. A survey of the literature indicated that P dioica and P racemosa are the best known species mainly because of their economic and pharmacological significance due to their chemical composition 5,7,8 …”
Section: Introductionmentioning
confidence: 99%